(untitled) (Revista de Letras, 2018)
The present study is part of a larger scale research (Guará-Tavares, 2011, 2013, 2016) that investigates the relationship among working memory capacity, pre-task planning and L2 speech performance. The aim of the study was to analyze whether higher working memory capacity individuals are better able to implement planned information into L2 oral performance of translation tasks. Learners’ planned ideas were accessed by means of think aloud protocols. Working memory capacity was measured by the Speaking Span Test. Results indicate that there are no signifi cant differences between higher and lower spans concerning retrieval of planned lexical items that were implemented into task performance. As for the percentage of clauses per c-unit retrieved, the differences between higher and lower spans only approached signifi cance. Results are discussed in terms of (Engle’s model of working memory (Engle, 1996; Engle & Oransky, 1999; Engle, Kane & Tuholsky, 1999).